Biology and immature stages of Pherbellia limbata (Diptera: Sciomyzidae), a parasitoid of the terrestrial snail Granaria frumentum - Nerudová-Horsáková, Jana; Murphy, William L.; Vala, Jean-Claude (Zootaxa, 2016)
The very rare Palaearctic Pherbellia limbata (Meigen, 1830) lives in limestone steppes and other xerothermic habitats in central and southern Europe. For the first time, the egg, first-, second- and third-instar larvae and the puparium are described. Scanning electron micrographs of various morphological features of immature stages are provided. Larvae of P. limbata are parasitoids exclusively of the terrestrial snail Granaria frumentum (Draparnaud, 1801). Results of this study are integrated with those of previous studies of the biology, ecology, immature stages, and mollusc-prey habitat of the other 28 (of 96) Pherbellia species for which life cycles have been completely or partially elucidated. Recent published taxonomic approaches to clarifying the phylogeny of the Sciomyzidae are discussed, particularly those involving DNA analyses of Pherbellia species.